Hazard stocks and expected returns - DeLisle, R. Jared; Ferguson, Michael F.; Kassa, Haimanot; Zaynutdinova, Gulnara R. (Journal of Banking & Finance, 2021)
Hazard stocks are the opposite of lottery stocks. We proxy hazard stocks with the minimum daily idiosyncratic return over the past month, “IMIN,” and examine the relation between hazard stocks and expected returns. The literature on lottery stocks implies that investors should discount hazard stocks. Anomalously, we find a negative relation between IMIN and future returns. Hedge portfolios that are long high IMIN stocks and short low IMIN stocks generate monthly alphas of -0.52% to -0.76%. The results are robust after controlling for numerous firm characteristics and corporate events. The hazard stock anomaly is primarily driven by limits to arbitrage and, to a lesser degree, by firm-level information uncertainty. Via the Reg SHO pilot program, we provide causal evidence that the apparent asymmetric preferences across lottery and hazard stocks are due to arbitrage asymmetry as described by Stambaugh et al. (2015). This demonstrates that asymmetric arbitrage may yield what appear to be asymmetric preferences.